(untitled) (Nepalese Journal of Ophthalmology, 2013)
Introduction: Chilled saline is commonly used to irrigate the ocular surface after photorefractive keratectomy (PRK) and is often considered by the patients to be uncomfortable. Room temperature (non-chilled) saline may be a safe and less painful alternative. Objectives: To compare pain and visual outcomes after irrigating the ocular surface with chilled saline versus room temperature saline in alcohol assisted PRK. Materials and methods: In this prospective, single-masked, randomized, contralateral eye study, myopic eyes were treated with PRK. Immediately after laser ablation one eye was irrigated with chilled saline and the other with non-chilled saline. Primary outcomes measured were pain, haze, uncorrected (UCVA) and best-corrected (BCVA) visual acuities, and manifest refraction. Results: Each group comprised of 40 eyes. There was no significant difference in pain between the groups at any point during five days after surgery. At 6 months the mean UCVA was -0.08 logMAR ± .077 [SD] (20/17) and -0.07 ± .074 logMAR (20/17) in the chilled and non-chilled groups respectively (p =.35). Both groups achieved 95% UCVA of 20/20 or better. The manifest refraction spherical equivalent (MRSE) was -0.05 ± 0.21 D and -0.025 ± 0.27 D respectively (p = .79). There were no lines lost of BCVA and no haze observed. Similar outcomes were observed with regard to pain and vision in both groups. Conclusion: The use of room temperature saline irrigation during PRK appears to be safe and effective. Nepal J Ophthalmol 2013; 5(10): 154-160 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8706